Deixis Analysis in Indonesian Politic on Social Media (A Case Study in Mata Najwa 3 Bacapres Talk Ideas in Najwa Shihab Youtube Channel) - Jupriaman, Jupriaman; Sahbuki Ritonga; Syafaruddin Siagian (CV. AFDIFAL MAJU BERKAH, 2023)
In spoken and written language, the use of deixis in society is often not fully understood by the person who is the speaker's speech partner because deixis is closely related to the context in which the speaker and speech partner communicate. Only the speaker and conversation partner understand the context and function of the deixis. The importance of understanding the use of deixis is to make speakers and speech partners understand what is meant and the messages conveyed and avoid misunderstandings. This research aims to examine the form of deixis used by Host Najwa Shihab and three candidate president of Republic Indonesia (Anies Baswedan, Ganjar Pranowo, Prabowo Subianto) in the Mata Najwa 3 Bacapres Talk Ideas on Najwa Shihab's Youtube Channel. This research method is a qualitative descriptive method. This research aims to analyze various kinds of deixis and functions occured in the speech utterances in the Mata Najwa three Bacapres Talk Ideas program which is live on the Najwa Shihab Youtube Channel. The data from this research are the speech utterances of the Host and three Presidential Candidates (Bacapres) (Anies Baswedan, Ganjar Pranowo, Prabowo Subianto) talking about Ideas as Presidential candidates of Republic Inodonesia 2024. The results of this research were demonstrative deixis, deixis of possessive/pronoun, deixis of circumstances of place and circumstances of time. The most frequently used deixis is possesive / pronoun deixis and the function deixis in the clause based on systemic functional linguistic realized as deictic in ideational function to specify nominal group and in textual function as reference.